Pengaruh Pendampingan Dan Pemberdayaan Masyarakat Terhadap Penerapan Protokol Kesehatan Dan Menyikat Gigi Malam Hari Pada Masa Pandemi (Sistem Monitoring Melalui Daring) - Endah Aryati Ekoningtyas; Hermien Nugraheni; Benni Benyamin (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2020)
Community empowerment is an effort to provide power (empowerment) or strengthening (strengthening) to the community. Community empowerment is defined as the ability of individuals in the community forum to build community empowerment which aims to find new alternatives in community development. During a pandemic, family participation as a promotive, preventive and preventive approach is needed through the role of one family member to become mentoring whom a role model for the family to break the chain of Covit-19 disease. The research objective was to determine the effectiveness of the development of counseling through community empowerment with the approach of establishing Kader Mandiri Keluarga (KMK) as